Development and initial evaluation of the usefulness of a question prompt list to promote patients' level of information about work-related medical rehabilitation: a pilot study - Matthias Lukasczik; Hans Dieter Wolf; Heiner Vogel (Frontiers Media S.A., 2024)
IntroductionThe purpose of this study was to develop a question prompt list (QPL) to support patients undergoing work-related medical rehabilitation in obtaining relevant information and to explore how patients and physicians rate the QPL regarding its usefulness, practicability, and perceived (additional) effort.MethodsAn initial item pool was assessed by rehabilitation patients (N = 3) in cognitive interviews, rated by physicians and other health professionals (N = 11), and then further modified. The final QPL version (16 items) was used by patients (N = 36) in medical admission interviews in an inpatient medical rehabilitation facility and then evaluated. Physicians evaluated the QPL after each interview with a study participant (N = 6; k = 39 interviews).ResultsThe QPL was used by 50% of patients who rated its usefulness and comprehensibility positively. Neither the need for information nor satisfaction with the information received was correlated with QPL use. The physicians' assessment showed a positive evaluation regarding the provision of information and structuring of the conversation, but also a higher perceived time expenditure.DiscussionWhile initial testing of the QPL in work-related medical rehabilitation as a tool to support patient-provider communication generally showed a favorable evaluation by patients using it and physicians, future research should address its validity and effectiveness.